EFEK SITOTOKSIK PROTEIN DARI DAUN Mirabilis jalapa l HASIL PEMURNIAN DENGAN KOLOM CM SEPHAROSE CL-6B TERHADAP KULTUR SEL HeLa - Sudjadi, Sismindari, Ni Putu Ariantari, Zullies Ikawati, (University of Muhammadiyah Malang, 2010)
Mirabilis jalapa l leaves have been known containing Ribosome Inactivating Proteins (RIPs) base on its N-glycosidase activity and cleavage of supercoiled double stranded DNA. The research aims to investigate cytotoxic activity of protein isolated from Mirabilis jalapa l leaves against HeLa cell culture. In this research, crude extract of Mirabilis jalapa l leaves was separated by gradual precipitation using sulphate ammonium followed by dyalisis. Further separation of protein fraction with cation exchange chromatography using CM sepharose CL-6B column and elution with sodium phosphate buffer 5 mM pH 6,5 for 30 minutes continued with sodium phosphate buffer 5 mM pH 6,5 containing 0-0,5 M NaCl by gradient elution for 90 minutes. Cytotoxicity activity testing of protein fraction that showed an ability to cleave supercoiled double stranded DNA revealed that RIPs eluated at NaCl gradient of 0,33-0,37 M and 0,38-0,41 M, concentration of 0,553 mg/mL relatively less toxic against HeLa cell culture with percentage of cytotoxicity of 29,53%.Â Keywords: Mirabilis jalapa l, RIPs, cytotoxicity